Involvement of a Putative Bipartite Transit Peptide in Targeting Rice Pheophorbide a Oxygenase into Chloroplasts for Chlorophyll Degradation during Leaf Senescence. (20th March 2016) - Xie, Qingjun; Liang, Yan; Zhang, Jian; Zheng, Huakun; Dong, Guojun; Qian, Qian; Zuo, Jianru
Abstract: Leaf senescence is one of the major factors contributing to the productivity and the grain quality in crops. The regulatory mechanism of leaf senescence remains largely unknown. Here, we report the identification and characterization of a rice ea rlys enescence 1 ( eas1 ) mutant, which displayed an early leaf senescence phenotype, accompanying by dwarfism and reduced tiller number, eventually leading to the reduction of grain yield. Map-based cloning revealed that the nuclear gene EAS1 encodes a pheophorbide a oxygenase (PaO), a key enzyme for chlorophyll breakdown. A highly conserved Thr residue of PaO was mutated into Ile in the eas1 mutant. Phylogenetic analysis indicates that PaO is an evolutionarily conserved protein, and EAS1 is 68% identical to the Arabidopsis ACCERLERATED CELL DEATH (ACD1) protein. Unlike ACD1 that contains a single transit peptide, EAS1 contains two putative transit peptides at its N-terminus, which are essential for its functionality, suggesting that targeting of EAS1 to the chloroplast is likely mediated by a putative bipartite transit peptide. Consistently, only a short version of EAS1 lacking the first putative transit peptide, but not the full-length EAS1, was capable of rescuing the Arabidopsis acd1 mutant phenotype. These results suggest that rice EAS1 represents a functional PaO, which is involved in chlorophyll degradation and may utilize a unique mechanism for its import into the chloroplast.